Development of Piety Through Community-Based Islamic Religious Education - Muhammad Muhson; Tobroni Tobroni; Faridi Faridi; Muhammad Nurhakim (AL-ISHLAH: Jurnal Pendidikan, 2024)
This study aims to describe and discover the uniqueness of piety through community-based Islamic Religious Education. Piety in this context is defined as human steadfastness in faith and its implementation, namely diligence in actualizing Islamic principles in life. This research is a qualitative study with a phenomenological approach. Data was collected through non-participant observation, semi-structured interviews, documentation, and literature review. The data analysis steps began with concrete description, experiencing the whole, creating units of meaning, transforming and reducing, creating constituents and structures, conveying findings, and interpreting findings. The collected data were tested for validity through source and technique triangulation. This study found that the religious experiences of the research subjects do not always come from family education. The religious community they belong to, the environment they live in, and demographic data also significantly contribute to their piety. Inner and spiritual experiences are dominant factors in the piety of research subjects. The development of piety among research subjects is influenced by their diverse experiences. For the research subjects, piety is interpreted as a principle of life. The true meaning of piety will give birth to a perspective and attitude of sincere devotion as a form of manifestation of true piety.